Initiierung von Smart Service Innovationen im produzierenden Gewerbe - Christoph Buck; Felicitas Kuch; Anna Lindenthal; Tobias Merktle; Anna Maria Oberländer; Christoph Tippel; Annette Wenninger (HMD Praxis der Wirtschaftsinformatik, 2022)
Essensbestellungen, die ein Kühlschrank automatisiert vornimmt oder Kochrezepte, die ein Kühlschrank basierend auf dem Kühlschrankinhalt vorschlägt~– das sind Beispiele für Smart Services. Diese Art Services sind an den Kunden angepasste, digitalisierte Lösungen, welche innovative Wertangebote und digitale Geschäftsmodelle ermöglichen. Sie vertiefen die Beziehung zwischen Kunden und Unternehmen, eröffnen darüber neue Marktchancen und bilden die Grundlage für Service-Ökosysteme. Trotz der vielfältigen Möglichkeiten stellt die Generierung von Smart Service Innovations-Ideen für Unternehmen eine komplexe Herausforderung dar. Die Komplexität ist auf die verschiedenen involvierten Akteure sowie die physischen und digitalen Komponenten einer Smart Service Innovation zurückzuführen. Um Unternehmen bei der Initiierung von Smart Service Innovationen zu unterstützen, stellt dieser Beitrag die relevanten Akteure und Komponenten von Smart Services vor. Außerdem untersucht der Beitrag, wie Unternehmen systematisch zu ihren Kunden und vorhandenen Ressourcen passende Smart Service Innovations-Ideen generieren können. Anhand eines Innovationsprojekts mit einem Unternehmen aus dem produzierenden Gewerbe werden praxisrelevante Erkenntnisse über eine Vorgehensweise zur Initiierung von Smart Service Innovationen abgeleitet. Außerdem werden Handlungsempfehlungen für Unternehmen ausgesprochen, die vor ähnlichen (Innovations‑) Herausforderungen stehen und eine gezielte Entwicklung von Smart Service Innovationen ergänzend zum bestehenden Produkt- und Service-Portfolio anstreben. Dies bietet Unternehmen Ansatzpunkte für die Anbindung an digitale Märkte und Service-Ökosysteme sowie für die ökonomisch nachhaltige Stärkung ihrer Wettbewerbsfähigkeit mithilfe von Smart Service Innovationen. Abstract: Food orders that a~refrigerator automates or cooking recipes that a~refrigerator suggests based on the contents of the refrigerator—these are examples of smart services. These types of services are digitized solutions adapted to the customer that enable innovative value propositions and digital business models. They deepen the relationship between customers and companies, open up new market opportunities and form the basis for service ecosystems. Despite the wide range of possibilities, generating smart service innovation ideas is a~complex challenge for companies. The complexity is due to the various actors involved as well as the physical and digital components of a~smart service innovation. To help companies initiate smart service innovation, this paper introduces the relevant actors and components of smart services. In addition, the paper examines how companies can systematically generate smart service innovation ideas that match their customers and existing resources. Based on an innovation project with a~company from the manufacturing sector, practice-relevant insights into a~procedure for the initiation of smart service innovations are derived. In addition, recommendations for action are made for companies facing similar (innovation) challenges and striving for a~targeted development of smart service innovations to complement their existing product and service portfolio. This offers companies starting points for connecting to digital markets and service ecosystems and for strengthening their competitiveness in an economically sustainable manner with the help of smart service innovations. – – Food orders that a~refrigerator automates or cooking recipes that a~refrigerator suggests based on the contents of the refrigerator—these are examples of smart services. These types of services are digitized solutions adapted to the customer that enable innovative value propositions and digital business models. They deepen the relationship between customers and companies, open up new market opportunities and form the basis for service ecosystems. Despite the wide range of possibilities, generating smart service innovation ideas is a~complex challenge for companies. The complexity is due to the various actors involved as well as the physical and digital components of a~smart service innovation. To help companies initiate smart service innovation, this paper introduces the relevant actors and components of smart services. In addition, the paper examines how companies can systematically generate smart service innovation ideas that match their customers and existing resources. Based on an innovation project with a~company from the manufacturing sector, practice-relevant insights into a~procedure for the initiation of smart service innovations are derived. In addition, recommendations for action are made for companies facing similar (innovation) challenges and striving for a~targeted development of smart service innovations to complement their existing product and service portfolio. This offers companies starting points for connecting to digital markets and service ecosystems and for strengthening their competitiveness in an economically sustainable manner with the help of smart service innovations.
Keywords: 000; Smart Service; Service-Ökosystem; Digitales Geschäftsmodell; Produzierendes Gewerbe; Service Ecosystem; Digital Business Model; Manufacturing Industry